Variation in parental rearing expenditure triggers short‐term physiological effects on offspring in a long‐lived seabird. (16th February 2016) - González‐Medina, Erick; Castillo‐Guerrero, José Alfredo; Santiago‐Quesada, Francisco; Villegas, Auxiliadora; Masero, José A.; Sánchez‐Guzmán, Juan M.; Fernández, Guillermo
Abstract : Parental care in long‐lived bird species involves a trade‐off between the benefits of increasing the effort expended on current offspring and the costs that this represents for future reproductive output. Under regimes of high environmental variability, long‐lived seabirds can adjust their breeding effort to buffer the negative effects of this variability on their offspring. However, the potential impacts of variation in breeding effort on offspring physiology in the short term and on longer‐term survival are poorly understood. In this study, we manipulated brood age through a cross‐fostering experiment to assess whether increasing or decreasing parental reproductive expenditure led to costs in Blue‐footed Booby Sula nebouxii chicks. Specifically, we tested the consequences of altered parental reproductive expenditure on the offspring's physiological condition (plasma metabolites, heterophil to lymphocyte ratio (H/L) and body condition index (BCI)) and survival. Offspring from broods in which parental investment was experimentally increased showed a lower BCI and lower alkaline phosphatase levels and higher H/L ratios than controls. Conversely, offspring showed the opposite pattern when reproductive expenditure was experimentally decreased. We observed no effects of manipulation of parental investment on triglyceride levels or on survival rates. Although our findings suggest that Blue‐footed Booby parents have the ability to adjust their breeding effort according to the demands of their offspring, parental effort could influence the effect of hatching order by suppressing the aggressive tendency of the senior chick.